Dzielnica VII Zwierzyniec: Historia - ludzie - kultura (Księgarnia Akademicka Publishing, 2024)
DISTRICT VII ZWIERZYNIEC: HISTORY – PEOPLE – CULTURE The structure and urban layout of Krakow is the result of centuries of evolution, and the current territory of the city includes not only the former, so-called "Sarmatian Tri-City" or even "Penta-City" but also the entire mosaic of jurydyki and villages surrounding it in the past, constituting to a large extent a single economic space. Some of them - Zwierzyniec with Salwator, Półwsie Zwierzynieckie together with Błonia, Chełm and Zakamycze, Przegorzały, Wola Justowska with Wolski Forest, Bielany and Olszanica - currently from District VII of Krakow. Its past is inextricably linked with the history of the inhabitants of the former villages, subjects to various superior authorities - monastic, clerical, noble, royal and municipal. The book was written by historians, regionalists and archeologists associated with and originating from the Krakow scientific community. The aim of it is to present the prehistory and history of the area that is currently District VII Zwierzyniec. The time frame of the study is wide and covers the period from prehistory to the preesent day. It is worth nothing that this is the first attempt so far to comprehensively discuss the history of a modern district of Krakow in a monographic outline and present its multi-threaded history, including such issues as its changing limits, administrative, settlement, economic, social, communication, educational and cultural developments, and dozens of others.